The Correlation Between Instagram Social Media Use Intensity and Anxiety Levels of Nursing Students of Universitas Muhammadiyah Purwokerto - Ghariza Amalia; Meida Laely Ramdani (UM Purwokerto Press, 2022)
Background: The use of social media can enhance interpersonal relationships, serve as a medium for personal growth and expression, and expand knowledge and information. However, social media use can also impact a person's self-esteem, quality of life, academic performance, Body Mass Index, and, most importantly, psychological diseases such as depression. The high rates of anxiety and sadness among students can be affected by the excessive use of social media.. Objective: This research to identify the correlation between To determine the correlation between the intensity of using Instagram social media and the level of anxiety in Nursing Students at Universitas Muhammadiyah Purwokerto. Method: Cross-sectional approach was used as the research method. The sample of this research is the 6th semester of Nursing Students with Proportional Random Sampling Technique with 72 respondents. Chi-Square Test was used to analyze the data. Results: The average age of the respondents was 21 years, and 58 were primarily female. There is a correlation between the intensity of students' Instagram use; the Medium category as many as 36 (50%) respondents. At the Student Anxiety Level, 47 (65.3%) respondents were in the Moderate Anxiety category, with the Chi-Square test results obtaining a p-value = 0.001 (p<0.05). Conclusion: The prevalence of Instagram among social media users impacts nursing students' anxiety levels. According to the findings of this study, there was a correlation between the students' anxiety levels and their intensity of the use of Instagram social media at Universitas Muhammadiyah Purwokerto.